Static and dynamic magnetic properties and effect of surface chemistry on the morphology and crystallinity of DyCrO3 nanoplatelets - Gupta, Preeti; Bhargava, Richa; Das, Raja; Poddar, Pankaj (RSC Advances, 2013)
In this contribution, the structural and magnetic properties of DyCrO3 nanoplatelets, synthesized by a hydrolytic sol-gel method, have been investigated. The crystalline phase of DyCrO3 was attained at the decomposition temperature of 800 degrees C for citric acid and oxalic acid, respectively and their structural analysis indicates a distorted orthorhombic perovskite structure of the DyCrO3 nanoplatelets. The dc-magnetization curve shows the Neel temperature of similar to 144 and similar to 146 K for DyCrO3 nanoplatelets synthesized using citric acid (DCO (C)) and oxalic acid (DCO (O)), respectively. In addition, DCO (O) shows weak anomalies at similar to 22 and similar to 6 K in the zero-field-cooled and field-cooled magnetization curves. Below the Neel temperature, DCO (C) and DCO (O) exhibit cross-over from positive to negative magnetization at similar to 143 and similar to 145 K, respectively. This was attributed to a Dy3+-Cr3+ interaction, which resulted in a weak ferromagnetic coupling (seen as a small opening in the M-H curves). The low temperature transition observed at similar to 6 K can be assigned to the onset of Dy3+-Dy3+ antiferromagnetic interaction.